The potential impact of a single amino‐acid substitution on the efficacy of equine influenza vaccines. (3rd June 2014) - Yamanaka, T.; Cullinane, A.; Gildea, S.; Bannai, H.; Nemoto, M.; Tsujimura, K.; Kondo, T.; Matsumura, T.
Summary Reasons for performing study The protection induced by an equine influenza (EI) vaccine strain depends on its antigenic relatedness to the challenge virus. Although the World Organisation for Animal Health (OIE) recommend that both Florida sublineage clade 1 (Fc1) and clade 2 (Fc2) viruses should be included in EI vaccines, Japanese EI vaccines have not, thus far, been updated to include a Fc2 virus. Objectives To evaluate the efficacy of antibodies raised against Japanese EI vaccine strains in the neutralisation of recent Fc2 viruses. Study design Antigenic analysis. Methods Virus neutralisation tests were performed using antisera from experimentally infected horses and from horses that had received a primary course of the currently available vaccines. Results Antiserum raised against the Japanese EI vaccine strain, A/equine/La Plata/1993, exhibited poor cross‐neutralising activity against the Fc2 viruses isolated recently in Ireland and the UK, which have the substitution of alanine to valine at position 144 in antigenic site A of the haemagglutinin gene. In contrast, the antiserum exhibited good cross‐neutralising activity against the Fc2 viruses without the substitution. This finding was supported in experiments with antisera collected from vaccinated horses. Conclusions This suggests that the efficacy of the Japanese EI vaccine for some of the recent Fc2 viruses is suboptimal and that vaccines should be updated in accordance with the OIE recommendations.